PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF COGNITIVE ABILITIES IN FUTURE SPORTS COACHES (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The development of cognitive abilities of future sports coaches is a pedagogical and psychological process aimed at strengthening their mental processes, such as attention, memory, thinking, and decision-making. High cognitive abilities allow coaches to effectively analyze complex situations, plan training sessions, and communicate effectively with players. Active learning, reflective exercises, and self-assessment are used as pedagogical methods. Psychological support, stress management, and increased motivation also contribute to the improvement of cognitive processes. As a result, the development of cognitive abilities increases the professional potential of sports coaches and positively influences the success of sports teams.